Understanding Community Perceptions of the St. Kitts’ “Monkey Problem” by Adapting Harm Reduction Concepts and Methods - Gallagher, Christa A.; Hervé-Claude, Luis Pablo; Cruz-Martinez, Luis; Stephen, Craig (Frontiers in Ecology and Evolution, 2022)
Wicked problems in One Health are associated with dynamicity and uncertainty that require experts, authorities and community members to reach for innovative means of collective inquiry, and collaborative interventions to address the deep social issues at the root of interspecies problems. In this study we explore the value of harm reduction concepts to understand a hundreds of year old issue, the St. Kitts’ “monkey problem”, which involves the invasive African green monkey (Chlorocebus sabaeus) as the cause of deleterious effects on agriculture, but concurrent positive effects on tourism and biomedical research. The harm reduction approach, a systems and settings-based approach with decades of success in public health, can serve as a framework to produce action on persistent societal problems. Harm reduction concepts and methods and participatory epidemiology were used to uncover local perceptions about human-monkey interactions and “meet people where they are” by asking the research question: Are there commonalities in perceptions and values linked to the St. Kitts’ “monkey problem” that are shared across diverse representatives of society that can act as a common starting place to launch collaborative responses to this invasive species? Through a series of focus group activities and interviews we found that the Kittitian “monkey problem” is a contentious and dichotomous problem pervasive in most of society that has no single stakeholders nor one solution. Harm reduction helped to map the island’s human-monkey system and elucidated an entry point towards tackling this problem through the identification of shared values, and also provided a model for incremental gains that may be achieved. Likening the St. Kitts “monkey problem” to a wicked problem enabled stakeholders to seek more options to manage the problem rather than to conclusively solve it. Frequently mentioned shared values including the protection of farmer crops and backyard harvests likely represent strong entry points to this problem and a jumping-off point to begin collective action towards future improvements.